Design and simulation of a non-resonant antenna: waveguide slot antenna for 30 GHz - Óscar I Montiel; Mario A. Ayala; Lácides Ripoll S. (Visión Electrónica, 2016)
The main contribution of this article is the design and simulation of a non-resonant slot antenna based on wave guides to operate in the range of microwaves. The design is done using MATLAB and the Chebyshev synthesis to determine the distribution of current in each element. Based on this information, the size and distribution of the elements are calculated. Different design conditions are simulated, such as: changes in the level from main lobe to secondary and dierent number of slots at one frequency. The slots are interleaved with respect to the axis of the waveguide and separated by a distance (d). To determine its dimensions, it is necessary to deduce the conductances of the array. A particular design case is compared with simulations from the software CST Microwave Studio. It is observed that radiation diagrams are very similar in both number and amplitude of the lobes, validating the tool used.